Supplementation with Combined Additive Improved the Production of Dairy Cows and Their Offspring with Maintenance of Antioxidative Stability - Hongxing Zhang; Yiliyaer Nuermaimaiti; Kebi Hao; Yan Qi; Yiming Xu; Yimin Zhuang; Fei Wang; Guobin Hou; Tianyu Chen; Jianxin Xiao; Gang Guo; Yajing Wang; et al. (MDPI AG, 2024)
Oxidative stress damage in periparturient cows decreases both production and their health; supplementation with complex additives during the periparturient period has been used as an important strategy to enhance the antioxidant status and production of dairy cows. The periparturient cows not only risk a negative energy balance due to reduced dry matter intake but also represent a sensitive period for oxidative stress. Therefore, we have developed an immunomodulatory and nutritional regulation combined additive (INC) that hopefully can improve the immune status and production of cows during the periparturient period and their offspring health and growth by improving their antioxidant stress status. The INC comprised a diverse array of additives, including water-soluble and fat-soluble vitamins, Selenomethionine, and active dry Saccharomyces cerevisiae. Forty-five multiparous Holstein cows were randomly assigned to three treatments: CON (no INC supplementation, n = 15), INC30 (30 g/d INC supplementation, n = 15), and INC60 (60 g/d INC supplementation, n = 15) based on last lactation milk yield, body condition score, and parity. Newborn calves were administered 4 L of maternal colostrum originating from the corresponding treatment and categorized based on the treatment received by their respective dams. The INC not only served to maintain the antioxidative stress system of dairy cows during the periparturient period but also showed a tendency to improve the immune response (lower tumor necrosis factor and interleukin-6) during the perinatal period. A linear decrease in concentrations of alkaline phosphatase postpartum and β-hydroxybutyrate was observed with INC supplementation. Milk fat yield, milk protein yield, and energy-corrected milk yield were also increased linearly with increasing additive supplementation. Calves in the INC30 group exhibited greater wither height and chest girth but no significant effect on average daily gain or body weight. The diarrhea frequency was linearly decreased with the incremental level of INC. Results indicate that supplementation with INC in peripartum dairy cows could be a major strategy to improve immune response, decrease inflammation, maintain antioxidant stress status in transition dairy cows, and have merit in their calves. In conclusion, this study underlines the benefits of INC supplementation during the transition period, as it improved anti-inflammatory capacity, could positively impact antioxidative stress capacity, and eventually enhanced the production performance of dairy cows and the health and growth of calves.